EFFECT OF LOCAL PROBIOTIC-ENRICHED COMMERCIAL FEED ON GROWTH PERFORMANCE AND SURVIVAL RATE OF SIAMESE PANGASIUS (Pangasianodon hypophthalmus) FRY - Rumondang, Anne; Huda, Mhd Aidil; Panggabean, Nabilah Hanun (Universitas Mataram, 2025)
The application of local probiotics in commercial feed not only contributes to aquaculture efficiency but also opens up opportunities for utilizing inexpensive and easily accessible local materials as alternative environmentally friendly feed additives. Biologically, probiotics work by enhancing the balance of intestinal microflora, improving nutrient absorption, and strengthening the fish's immune system against environmental stress and pathogenic infections. Through this mechanism, the inclusion of local probiotics in feed can be an effective approach to naturally and sustainably enhance the physiological performance of fish fry. This study aimed to determine the effect of adding locally-sourced probiotics to commercial feed on the growth and survival of Siamese Pangasius (Pangasianodon hypophthalmus) fry. The probiotics were formulated using local ingredients such as banana fronds, turmeric, fine rice bran, yeast, molasses, and Yakult, and were applied to commercial feed at various concentrations. The research was conducted experimentally using a Completely Randomized Design (CRD) with four treatments and three replications: P0 (control, no probiotics), P1 (10 mL probiotics/kg feed), P2 (20 mL/kg feed), and P3 (30 mL/kg feed). Observed parameters included growth, feed conversion ratio (FCR), and survival rate (SR). The results showed that treatment P2 yielded the best outcomes, with the highest growth rate, lowest FCR, and significantly higher survival rate compared to the control. In conclusion, enrichment of commercial feed with local probiotics at a dosage of 20 mL/kg significantly improved the growth performance and survival of Siamese Pangasius fry (p<0.05).